2019
DOI: 10.3390/cryst9050253
|View full text |Cite
|
Sign up to set email alerts
|

Protein Crystallization in Ionic-Liquid Hydrogel Composite Membranes

Abstract: Protein crystallization is a powerful purification tool. It is the first step for crystallographic structural investigations, and can be preparatory for biotechnological applications. However, crystallizing proteins is challenging and methods to control the crystallization process are needed. Ionic-liquid hydrogel composite membranes (IL-HCMs) have been used here as material capable of supporting protein crystallization and hosting grown crystals. We found that IL-HCMs affect the selection mechanism of glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Crystals grow completely immersed in the hydrogel layer, probably by the specific interaction of proteins with the ionic liquids. This growth has shown to have an influence on space group and polymorphism [99].…”
Section: Particular Characteristics Of Protein Crystal Growthmentioning
confidence: 99%
“…Crystals grow completely immersed in the hydrogel layer, probably by the specific interaction of proteins with the ionic liquids. This growth has shown to have an influence on space group and polymorphism [99].…”
Section: Particular Characteristics Of Protein Crystal Growthmentioning
confidence: 99%
“…In the last few decades, researchers have focused on synthesizing nanocomposite hydrogels for tissue engineering, drug delivery, antimicrobial, bioactive electrode coatings, actuators, and sensors [1][2][3][4]. Nanocomposite hydrogels are advantageous with softness, biocompatibility, multi-functionality, and adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(sodium 4-styrenesulfonate) ZnO [28] Poly(Citric Acid-co-Glycerol) CaCO 3 [99] Itaconic acid-2-acrylamido-2-methylpropanesulfonic acid allyl polyoxyethylene ether copolymer CaCO 3 [100] Organic polymer Struvit [101] Regiorandom pentacene-bithiophene, poly(3-hexylthiophene) 6,13-bis(triisopropylsilylethynyl)pentacene [102] Poly(ethylene glycol) Perovskite [104] Poly(3-hexylthiophene), poly(methyl methacrylate) Bis(triisopropylsilylethynyl) pentacene [108] Maleic acid and sodium ρ-styrenesulfonate copolymer CaSO 4 •2H 2 O [109] Poly(N-vinyl pyrrolidone) copolymers H 2 O [113] Composite membranes Glucose Isomerase [117] In conclusion, the authors would like to emphasize that the branch of science tackling complicated interactions between crystallizing solutions and polymer additives becomes currently more and more important from both theoretical and practical points of view and therefore is a promising area for further research.…”
Section: Crystal Surface Screening/nucleation Inhibitionmentioning
confidence: 99%
“…Profio et al demonstrated the fabrication of hydrogel membranes displaying controlled chemical composition and nanostructure in the creation of crystals with enhanced diffraction properties at a lower protein concentration than the conventional technique [ 116 ]. Belviso et al used ionic-liquid hydrogel composite membranes as material for supporting protein crystallization [ 117 ]. They proved that protein crystallization by ionic-liquid hydrogel composite membranes had the potential for biotechnological applications and could contain crystallized enzymes in working conditions.…”
Section: Present and Future Perspectives Of Applications Of Crystallization Phenomena In The Presence Of Polymersmentioning
confidence: 99%